A judicialização de medicamentos no Espírito Santo : os desafios na construção da política pública de assistência farmacêutica - Silva, Arielle Rocha de Oliveira (2012)
This paper analyzes the growing use of lawsuits demanding medicines through the Brazilian Health System (SUS), known as the Litigation in Pharmaceutical Service. It also seeks to interrogate the relationship between this litigation and the construction and practice of Public Policy for Pharmaceutical Services ES. Therefore, present the main issues related to the growing these lawsuits, under the eyes of various involved in the process. Thus, aims to highlight the faces and interfaces of the Litigates found in the discourses and practices of justice, doctors, managers and users pharmaceutical services in the context of the state of Espírito Santo. This study seeks to depart from the practices of knowledge judges, who take upon themselves the duty to say who is right or wrong. In contrast, the objective is to analyze the production process demand of Litigations Pharmaceutical Services. Through review and analysis of available published research on the subject, it is realized that the approaches on the subject, as well as management actions aimed at their combat, mostly do not involve the user experience, a key element in this research. It is observed that the medicine litigation, through the varied aspects, narratives and experiences that constitute it, cannot be analyzed without considering it multiple and multifaceted character. The analyzes also points to the importance of strengthening a Pharmaceutical Assistance Policy more committed to the singular demands, so that, in the midst of its protocols and standards, affirms an ethical and common posture.